Ten black dots - Crews, Donald (New York : Greenwillow Books, 1986)
A counting book which shows what can be done with ten black dots--one can make a sun, two a fox's eyes, or eight the wheels of a train.
"Redesigned and revised."
Keywords: Counting; Stories in rhyme